Self-focused attention and safety behaviours maintain social anxiety in adolescents: an experimental study - Leigh, E; Chiu, K; Clark, DM (Public Library of Science, 2021)
Background Self-focused attention and safety behaviours are both associated with adolescent social anxiety. In adults, experimental studies have indicated that the processes are causally implicated in social anxiety, but this hypothesis has not yet been tested in a youth sample.